Seni untuk Hati: Art Therapy sebagai Penguatan Emosi Anak di Panti Asuhan Guyub Rukun - Alwi, Wiwit; Danu Rahmat Fajari; Destry Ramadanti; Ferdianata Gustafian; Imallatul Istma; Kurnia Mutiara Indah; Melse Yesnaini; Nadia Razela; Putri Indah Pratiwi; Rafika Fadhila Dhani; Revi Alvionita; Sinta Annisa Putri; Waqina Nata; Yensi Pertamasari (Andromeda: Jurnal Pengabdian Masyarakat Rafflesia, 2025)
The activity "Art for the Heart: Art Therapy as Emotional Empowerment for Children at the Guyub Rukun Orphanage" was implemented as an application of art-based Guidance and Counseling to enhance the emotional well-being of orphanage children. These children often face psychosocial challenges due to the lack of affection and past traumatic experiences. Art therapy was chosen as a method because it allows children to express their emotions freely and creatively through artistic media. This study employed a descriptive qualitative method with a participatory approach through socialization sessions and hands-on practice. The results showed that the children demonstrated high enthusiasm and were able to express their feelings through activities such as drawing, coloring, and collaborative art projects. The program provided a safe space for emotional exploration and also improved social skills, self-confidence, and mutual respect. Furthermore, the activity increased caregivers’ awareness of the importance of creative approaches in supporting children. In conclusion, art therapy is proven to be an effective strategy within Guidance and Counseling to strengthen the emotional capacity of orphaned children and is recommended for sustainable implementation. Keywords: Art therapy; guidance and counseling; children's emotions; orphanage; psychological well-being